2016
DOI: 10.2174/1381612822666160715131359
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Nanosystems to Prostate Cancer

Abstract: Prostate cancer remains an increasingly common malignancy worldwide. Many advances in drug development have been achieved for the conventional treatments; however, chemotherapeutic agents are distributed nonspecifically in the body where they affect both prostate cancer and healthy cells. Limited dose achievable within the prostate tumor and suboptimal treatment due to excessive toxicities reveal the importance of the development of more specific mechanisms and ways of drug targeting to prostate tumor. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These findings are consistent with earlier research, which indicated that the internalization and subsequent intracellular release of the anticancer drug from NPs is responsible for the cytotoxic effect of NPs ( Zaki, 2014 ). It is proposed that this formulation (niosome and magnetic niosome) can increase the drug bioavailability which can induce cancer cell apoptosis by causing DNA damage or the oxidation of proteins, lipids, and enzymes, resulting in cell death and also helping to destroy and inhibit the mitochondrial respiratory complex ( Rodrigues Pereira da Silva et al, 2016 ; Van Houten et al, 2016 ; Juan et al, 2021 ). El-Far and co. argued that the cytotoxicity percentage by IC50 value between paclitaxel–metal NPs–NIOs and oxaliplatin–metal NPs–NIOs at the same concentrations did not differ significantly (pH 0.5).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with earlier research, which indicated that the internalization and subsequent intracellular release of the anticancer drug from NPs is responsible for the cytotoxic effect of NPs ( Zaki, 2014 ). It is proposed that this formulation (niosome and magnetic niosome) can increase the drug bioavailability which can induce cancer cell apoptosis by causing DNA damage or the oxidation of proteins, lipids, and enzymes, resulting in cell death and also helping to destroy and inhibit the mitochondrial respiratory complex ( Rodrigues Pereira da Silva et al, 2016 ; Van Houten et al, 2016 ; Juan et al, 2021 ). El-Far and co. argued that the cytotoxicity percentage by IC50 value between paclitaxel–metal NPs–NIOs and oxaliplatin–metal NPs–NIOs at the same concentrations did not differ significantly (pH 0.5).…”
Section: Resultsmentioning
confidence: 99%